Issues on Arabic Scriptures in Malay/Indonesia Language: A Study of its Contributions in the Development of Regional Culture, Language & Literature Literacy - Kembaren, Mardiah Mawar; Noor, Noordin Mohd; Lubis, M. Husnan (Talenta Publisher, 2019)
This paper touches on the important role of Islam in Malay literature and culture literacy, in the region. Malay literary and cultural treasures that were originally oral traditions have changed after the local community has embraced the teachings of Islam that bring along the Arabic scripture or Arabic writing system. This system of Arabic writing has greatly influenced Malay literature and culture. This paper therefore explores academically the role, contribution and discussion regarding the future of Arabic Scripture in the region. It would not be too much to say that it was the Arabic writing system that made the Malay community illiterate. This paper is expected to benefit not only to those who study literature and linguistic but for those with a background in Islamic studies too to study the regional literature and culture, especially those related to Malay studies.